Error Estimate of Data Dependence for Discontinuous Operators by New Iteration Process with Convergence Analysis. (26th October 2019) - Kumam, Wiyada; Khammahawong, Konrawut; Kumam, Poom
Abstract: In this paper, we introduce a new discontinuous operator and investigate the existence and uniqueness of fixed points for the operators in complete metric spaces. We also provide rate of convergence and data dependency of S-iterative scheme for a fixed point of the discontinuous operators in Banach spaces. Moreover, we prove the estimation Collage theorems and compare error estimate between data dependency and Collage theorems. Numerical examples are provided to support our results.